Entomological efficacy of durable wall lining with reduced wall surface coverage for strengthening visceral leishmaniasis vector control in Bangladesh, India and Nepal. Issue 1 (December 2016) - Huda, M.; Kumar, Vijay; Das, Murari; Ghosh, Debashis; Priyanka, Jyoti; Das, Pradeep; Alim, Abdul; Matlashewski, Greg; Kroeger, Axel; Alfonso-Sierra, Eduardo; Mondal, Dinesh
Abstract Background New methods for controlling sand fly are highly desired by the Visceral Leishmaniasis (VL) elimination program of Bangladesh, India and Nepal for its consolidation and maintenance phases. To support the program we investigated safety, efficacy and cost of Durable Wall Lining to control sand fly. Methods This multicentre randomized controlled study in Bangladesh, India and Nepal included randomized two intervention clusters and one control cluster. Each cluster had 50 households except full wall surface coverage (DWL-FWSC) cluster in Nepal which had 46 households. Ten of 50 households were randomly selected for entomological activities ﻿except India where it was 6 households. Interventions were DWL-FWSC and reduced wall surface coverage (DWL-RWSC) with DWL which covers 1.8 m and 1.5 m height from floor respectively. Efficacy was measured by reduction in sand fly density by intervention and sand fly mortality assessment by the WHO cone bioassay test at 1 month after intervention. Trained field research assistants interviewed household heads for socio-demographic information, knowledge and practice about VL, vector control, and for their experience following the intervention. Cost data was collected using cost data collection tool which was designed for this study. Statistical analysis included difference-in-differences estimate, bivariate analysis, Poisson regression model and incremental cost-efficacy ratio calculation. Results Mean sand fly density reduction by DWL-FWSC and DWL-RWSC was respectively −4.96 (95 % CI, −4.54, −5.38) and −5.38 (95 % CI, −4.89, −5.88). The sand fly density reduction attributed by both the interventions were statistically significant after adjusting for covariates (IRR = 0.277, p  < 0.001 for DWL-RWSC and IRR = 0.371, p  < 0.001 for DWL-FWSC). The efficacy of DWL-RWSC and DWL-FWSC on sand fly density reduction was statistically comparable (p  = 0.214). The acceptability of both interventions was high. Transient burning sensations, flash on face and itching were most common adverse events and were observed mostly in Indian site. There was no serious adverse event. DWL-RWSC is cost-saving compared to DWL-FWSC. The incremental cost-efficacy ratio was −6.36, where DWL-RWSC dominates DWL-FWSC. Conclusions DWL-RWSC intervention is safe, efficacious, cost-saving and cost-effective in reducing indoor sand fly density. The VL elimination program in the Indian sub-continent may consider DWL-RWSC for sand fly control for its consolidation and maintenance phases.